Advancing adaptation of evidence-based interventions through implementation science: progress and opportunities - Chambers, David A. (Frontiers in Health Services, 2023)
While the recognition of the need to adapt interventions to improve their fit with populations and service systems has been well established within the scientific community, limited consideration of the role of adaptation within implementation science has impeded progress toward optimal uptake of evidence-based care. This article reflects on the traditional paths through which adapted interventions were studies, progress made in recent years toward better integration of the science of adaptation within implementation studies with reference to a special publication series, and next steps for the field to continue to build a robust knowledge base on adaptation.